Comparison of Ferrous Sulphate Versus Iron Polymaltose Complex in the Treatment of Iron Deficiency Anemia in Children - Saeed Zaman, Masud Murad Khan, Samina Tabussam, Sadaf Nawaz, Ammara Ayub, Sajid Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of ferrous sulphate versus iron Polymaltose complex (IPC) in the treatment of iron deficiency anemia (IDA) in children. Study Design: Randomized controlled trial. Place and Duration: Department of Pediatrics, Combined Military Hospital, Kharian Pakistan from Jan 2019 to Mar 2020. Methodology: A total of 150 children with IDA were included. At baseline, blood sample was obtained for assessment of hemoglobin level. Then children were randomly divided in two groups. In Group-A (n=75), patients were given ferrous sulphate while in In Group-B (n=75), IPC was given. After 12-weeks of treatment, hemoglobin level was assessed. Efficacy was labeled as “yes” if there was 2 g/dl hemoglobin improvement. Results: In a total of 150 children, the mean age in Group-A was 6.56±2.33 years and 6.05±2.78 years in Group-B. In group A, there were 37 (49.3%) males and 38 (50.7%) females while in Group-B there were 35 (46.7%) males and 40 (53.3%) females. At baseline in group A, the mean hemoglobin level was 6.07±1.12 g/dl while in group B, it was 6.16±1.14 g/dl. After 12-weeks, in Group-A the mean hemoglobin level was 9.44±1.61 g/dl whereas in Group-B, it was 8.83±2.01 g/dl (p=0.0420). There was insignificant difference observed for efficacy in both groups (p-value = 0.051). Practical Implications: Both IPC and ferrous sulphate resulted in significant rise in hemoglobin levels but ferrous sulphate showed better results in comparison to IPC. Conclusion: Although in comparison to IPC, ferrous sulphate resulted in significantly better rise in hemoglobin levels among children with IDA, but overall efficacy between the two studied drugs was relatively similar. Keywords: Ferrous sulphate, iron Polymaltose complex, iron deficiency anemia.